The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.mmcr.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Malassezia folliculitis in an infant

Abstract: Malassezia folliculitis commonly affects the adolescents and the young adults. We describe an unusual case of Malassezia folliculitis which is particular in age of patient and scare evolution of lesions. The patient was a three-month-old immuno-competent boy. On clinical examination, 1- to 2-mm superficial follicular pustules were observed on his face, neck and upper trunk. Direct microscopy of pustule scrapings and hair follicles showed numerous Malassezia yeast cells. Based on the clinical and mycological da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…To date, studies to determine which species of Malassezia may be involved in MF have yielded divergent results, with M. globosa , M. restricta , and M. sympodialis all recovered from hair follicles (Table ).…”
Section: Skin Diseases Associated With Malassezia Sppmentioning
confidence: 99%
“…To date, studies to determine which species of Malassezia may be involved in MF have yielded divergent results, with M. globosa , M. restricta , and M. sympodialis all recovered from hair follicles (Table ).…”
Section: Skin Diseases Associated With Malassezia Sppmentioning
confidence: 99%
“…Интересными наблюдениями, подтверждающими важную роль внешних и внутренних факторов в возникновении и утяжелении течения ВА, являются т. н. популяции, свободные от акне [47] Акне новорожденных встречаются приблизительно у 20% детей, возникают в первые 3-4 нед жизни ребенка, чаще у мальчиков [71]. Неонатальные акне важно отличать от акнеформных дерматозов и транзиторных состояний данной возрастной группы, в частности от неонатального цефалического пустулеза (neonatal cephalic pustulosis) и неонатального пустулярного меланоза (neonatal pustular melanosis), малассезия-фолликулитов [72,73]. В отличие от данных состояний, истинные акне характеризуются образованием комедонов, реже -появлением папул и пустул.…”
Section: роль влияния внешних и внутренних факторов на патогенез вульunclassified
“…The number of lesions can vary from few to more than one hundred (Figure 2). 3,11,18,19 Although different species may be involved, all species have the same clinical presentation. Clinically, MF is difficult to distinguish from bacterial folliculitis and acne vulgaris.…”
mentioning
confidence: 99%
“…Direct microscopical examination by 10%-20% KOH of pustules and follicular hairs can be used to confirm the diagnosis of MF, where an examination reveals abundant round spores budding yeast cells which supports the diagnosis (Figure 3). 5,19 Jacinto-Jamora et al graded the spore load per high-power field as shown in Table 1. Suzuki et al stated that MF was diagnosed when 10 or more yeast organisms per follicle (≥10 per visual field at 400 × magnification) were observed under direct microscopic examination.…”
mentioning
confidence: 99%
See 1 more Smart Citation